How to teach ethics to the undergraduates in clinical context? - Niaz, Khurram; Mahboob, Usman (Journal of the Pakistan Medical Association, 2022)
Teaching ethics to undergraduates is no more a part of hidden curriculum rather it is a norm to be incorporated in the formal curriculum. Regarding instructional strategies, the consensus is stagerry and mainly based on the institutional choices. To develop moral reasoning and address the social value system, Cognitive part is delivered through lecturing while affection part is discussed via reflective practices in small group settings through deliberate moral case teachings and portfolio note book writings. However the outcome of such practices is yet to be known. However we suggest that the ethical curriculum should base on the reflective practices, social constructivism and experiential learning. — Continue